Direct and indirect photolysis of seven micropollutants in secondary effluent from a wastewater lagoon. (October 2017) - Wang, Yufei; Roddick, Felicity A.; Fan, Linhua
Abstract: The photodegradation of seven micropollutants commonly found in municipal wastewater, namely caffeine, carbamazepine, diuron, simazine, sulfamethoxazole, triclosan and 2, 4-D, was investigated in pure water and secondary effluent to understand the direct and indirect photolysis of these compounds under natural sunlight irradiation. Sulfamethoxazole and triclosan were readily photodegraded with half-lives of 5.8 and 1.8 h, respectively, whilst the others were relatively resistant towards sunlight irradiation. Enhanced degradation was observed in secondary effluent compared with in the pure water matrix for all compounds, except for triclosan. It was confirmed that hydroxyl radicals played an important role in the photodegradation of the micropollutants while singlet oxygen may also play a role. The contribution of hydroxyl radical to the overall degradation of the five compounds that were resistant to direct sunlight accounted for 32%–70%. The impact of humic acid and nitrate, two known photosensitisers and wastewater components, on the photodegradation of the seven micropollutants in pure water was investigated under simulated solar radiation. The presence of nitrate promoted the photochemical loss of all seven micropollutants, however, humic acid caused promotion or inhibition, depending on the characteristics of the micropollutant. Humic acid enhanced the photolytic degradation of caffeine, sulfamethoxazole and diuron, while it hindered the photodegradation of the other four compounds by absorbing the available irradiation energy and/or reforming the parent compound. Furthermore, it was shown that there was only a small increase (up to 15%) in photodegradation of the compounds at 25 °C compared with that at 10 °C in the simulated system. Highlights: CAF, CBZ, DUR, SMZ and 2, 4-D primarily degraded via indirect photolysis. Hydroxyl radicals had important role in the indirect photolysis of five compounds. SMX and TCS primarily degraded via direct photolysis. Nitrate promoted the photolysis of all compounds while affected TCS & SMX slightly. Humic acid had differing effects on the photodegradation of the selected compounds.